Geomorphological Investigations in the Torngat Mountains of Northeastern Labrador-Ungava - Ives, J.D. (ARCTIC, 1957)
. The central area of study lay athwart the Labrador-Quebec boundary on the watershed between Nakvak Brook, which drains into Saglek Fiord, and the Koroksoak (Korok) River, which flows westwards into Ungava Bay. . Attention was concentrated on an extensive system of lateral moraines and kame terraces which slope eastwards from the watershed towards the head of Saglek Fiord. Similar systems were examined in the through-troughs to the south. The whole complex represents the late-Pleistocene limits of trunk glaciers flowing through the mountains towards the east and supplied by an ice cap of continental proportions west of the height of land. At this stage the higher summits stood as nunataks well above the level of the ice, and an extensive series of ice-dammed lakes was held against the western slopes of the highland finding outlets over ice-free cols into the Atlantic. Detailed studies in the watershed area provide a chronology of the final emergence of the area from the last ice sheet, and the draining of the ice-dammed lakes. A final stage was represented by a mass of ice in the lower valley of the Koroksoak which dammed a lake to the level of the col, at 1,050 feet, whence it drained into Nakvak Brook and ultimately into the Atlantic. Glacial erratics, found on summits up to 4,000 feet above sea level, corroborate the conclusions of the previous summer's work suggesting that at some stage the highest summits were inundated by ice flowing from the west. The data compiled from the two summers' work prompt the conclusion that during late-Pleistocene times the Torngat Mountains were influenced by two distinct glaciations, separated by an interglacial period of considerable intensity. The final glaciation, during which large areas remained ice-free, is tentatively correlated with the "classical" Wisconsin of central North America whereas the date of the preceding glacial period is uncertain. It may be the equivalent of the Illinoian Glaciation, or even be of post-Sangamon age, and in this case be comparable with a ...